'Not a museum piece': Exploring the 'special' occupational culture of religious broadcasting in Britain. (1st March 2014) - Noonan, Caitriona
Religion is often regarded as posing a distinct challenge to the occupational norms of cultural production and journalism due to its subjectivities and complexities. Based on research with staff involved in the production of content for BBC television and radio, this article explores the occupational context in which they work. In particular, it focuses on the experiences and strategies of the BBC's Department of Religion and Ethics as it attempts to secure its survival as an autonomous production unit. This group of executives, producers, presenters and production staff are in many ways unique because of the professional and social role that they fulfil, most notably through the close historical and ideological ties between religion and the principles of public service.This research finds a distinct professional identity built around a fusion of public service logic and commercialism, along with the mobilization of specialist knowledge. This allows the department to symbolically and discursively separate itself from other actors in this field as it attempts to reinforce religious broadcasting's professional distinctiveness at a crucial time in the survival of the unit and to highlight the uniqueness of religion as a topic within cultural production.